Probability and statistics for the engineering, computing, and physical sciences - Dougherty, Edward R. (Englewood Cliff, N.J. : Prentice Hall, 1990)
Written to accomplish 5 basic focus on contemporary applications, maintain a respectable mathematical level, provide a solid probabilistic framework, give a wide cross section of statistical techniques, and use examples that illustrate models and experimental situations relevant to the audience. Suitable for students with a standard undergraduate calculus background.
Includes index.
Keywords: Computing; Statistics